Pallidotomy for medically refractory status dystonicus in childhood. (4th April 2014) - Marras, Carlo Efisio; Rizzi, Michele; Cantonetti, Laura; Rebessi, Erika; De Benedictis, Alessandro; Portaluri, Francesco; Randi, Franco; Savioli, Alessandra; Castelli, Enrico; Vigevano, Federico
<x xml:space="preserve">Abstract</x> Aim Status dystonicus is a rare and potentially fatal condition of continuous and generalized muscle contraction that can complicate dystonia. As status dystonicus is usually refractory to traditional pharmacological therapy, alternative and invasive strategies have been developed, but so far there are no guidelines on status dystonicus management. Pallidotomy has shown good results in status dystonicus treatment. Method We report indications, surgical strategy, and outcome of bilateral pallidotomy in four pediatric patients (four males; mean age at surgery 11y 5mo) with secondary dystonia, who developed refractory status dystonicus. Pallidotomy was performed in the area corresponding to the mid portion of the globus pallidus internus. Results This procedure allowed patients to recover the pre‐status dystonicus condition, controlling dystonic postures and movements of trunk and limbs. Moreover oromandibular dystonia, which is resistant to conservative approaches and deep brain stimulation, was significantly reduced. No postoperative complications were registered. Interpretation Our study suggests pallidotomy as a feasible treatment in patients with secondary dystonia complicated by status dystonicus.